The Effect Of Financial Capability, Technology Usage And Prior Bank Experience Into Millenial Online Shopping Behavior - Kurniasari, Florentina; Abubakar, Arlyana (Publisher Cv. Inara, 2023)
The rapid development of technology has made all aspects of human life easier. Online shop is a form of change brought about by technological developments. With an online shop, humans can shop wherever and whenever. This convenience, of course, must be followed by sufficient financial capabilities because the ease of shopping that is not followed by good financial capabilities will cause new problems, especially financial problems. With a quantitative approach, researchers want to find out whether Financial Capability, Technology usage, and prior bank experience influence a person's online shopping behavior. The sample in this study were residents of Jakarta and Tangerang aged between 19-34 years. Data collection was carried out by distributing questionnaires through the Google Form. Meanwhile, to analyze, researchers used Smart-PLS 3.0 software. The results of the study concluded that financial capability has a positive effect on online shops, while technology usage and prior bank experience have no effect on online shops.